Kesalahan Morfologi Dalam Tulisan Yang Diunggah Di Instagram @riaricis1795 - Haruna, Nabilah; Puspa Mirani Kadir; Wagiati (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2023)
The majority of Indonesian people choose to use social media such as Instagram to channel their thoughts and feelings in the form of videos, and photos, then affixed with writing to describe the activities carried out. In this study, the researcher analyzed the morphological errors contained in the writing uploaded on Instagram @riaricis1795. This account was taken as the object of the data because it is included in top 10 the most popular celebrities who reached 34 million followers. Besides that, Ria Ricis is a role model for the young generation in Indonesia nowadays. This research aims to know how many mistakes were made by one of the country's celebrities when writing 'captions' on her personal Instagram page. The research method used is a descriptive analysis approach by observing and recording. Then, the data taken is limited to 30 uploads from a total of 560 that have been uploaded by @riaricis1795. The results of the analysis of the data found that there are 102 errors which include errors in the reduction of prefixes, and suffixes, omission of letters, use of uppercase and lowercase letters, improper reduplication words, separation and connection of words, and errors in abbreviating words.